Interaction between triphenylphosphine or 1,2-bis(diphenylphosphino)ethane with some complexes K[PtCl3(olefin)] (olefin: methyleugenol, safrole, isopropyl eugenoxyacetate) - Chien, Le Xuan; Chi, Nguyen Quynh; Dat, Nguyen Dang; Thanh Chi, Nguyen Thi (Vietnam Journal of Chemistry, 2017)
Novel study on the interaction between K[PtCl3(olefin)] (olefin: methyleugenol, safrole and isopropyl eugenoxyacetate) with TPP and DPPE shows that TPP and DPPE readily replace the olefins to form complexes [PtCl2(TPP)2] (P4), [PtCl2(DPPE)] (P5) and [Pt(DPPE)2]Cl2 (P6). P4 possesses trans configuration when the molar ratio of the mono olefin and TPP of 1:1. When the ratio is 1:2, P4 is a mixture of trans and cis isomers of which trans one is prevailing. The cis isomer trends to convert to trans one in chloroform solvent. P5 and P6 were formed when the molar ratio of mono isopropyl eugenoxyacetate and DPPE of 1:1 and 1:2, respectively. The structures of P4÷P6 were elucidated by Pt analysis, ESI-MS, IR and 1H NMR spectra studies. Keywords. Pt(II) complexes, olefins, phosphine derivatives